2016
DOI: 10.1002/ana.24708
|View full text |Cite
|
Sign up to set email alerts
|

Direct current stimulation induces mGluR5‐dependent neocortical plasticity

Abstract: We identify a novel molecular pathway by which tDCS modulates cortical excitability, and indicate a capacity for synergistic interaction between tDCS and pharmacologic mGluR5 facilitation. The findings support exploration of cathodal tDCS as a treatment of neurologic conditions characterized by aberrant regional cortical excitability referable to mGluR5-mTOR signaling. Ann Neurol 2016;80:233-246.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
50
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 51 publications
(199 reference statements)
4
50
0
Order By: Relevance
“…Thus, it was concluded that direct-current stimulation may be having its long lasting after-effects due to changes in the connections between neurons, like long-term potentiation (LTP) or long-term depression (LTD) are known to induce. More recent slice work appears to be consistent with this notion (Sun et al, 2016). …”
Section: Tdcs Can Last a Long Timementioning
confidence: 56%
See 1 more Smart Citation
“…Thus, it was concluded that direct-current stimulation may be having its long lasting after-effects due to changes in the connections between neurons, like long-term potentiation (LTP) or long-term depression (LTD) are known to induce. More recent slice work appears to be consistent with this notion (Sun et al, 2016). …”
Section: Tdcs Can Last a Long Timementioning
confidence: 56%
“…Cholinergic, serotonergic, and GABAergic systems have all been shown to be related to tDCS effects (Medeiros et al, 2012). Finally, recent slice work indicates that the long lasting after-effects of direct-current stimulation appears to be due to a molecular cascade involving metabotropic glutamate receptors, NMDA receptors, and GABA that induce long-term depression and potentiation (Sun et al, 2016). In sum, essentially every signaling pathway has been implicated in the molecular and cellular activity that gives rise to the effects we observe with tDCS delivered to human participants.…”
Section: Biophysical Basismentioning
confidence: 99%
“…mGluR2, mGluR3, and mGluR5 mature by 15 days after birth in rodents (human age: 0–24 months) [115]. Recent evidence indicates that cathodal tDCS-induced LTD is primarily mediated by mGluR5 receptors [116] and, thus, direct current stimulation protocols may not be less, if at all, effective during the first 2 years after birth in humans.…”
Section: Preclinical Insights Into the E:i Ratio In Developmentmentioning
confidence: 99%
“…Multiple mGlu 5 PAMs have robust efficacy in rodent models used to predict antipsychotic efficacy and the treatment of cognitive disturbances (Conn et al, 2009b; Liu et al, 2008; Parmentier-Batteur et al, 2014; Rook et al, 2013). Interestingly, mGlu 5 PAMs enhance induction of both long-term potentiation (LTP) and long-term depression (LTD) at excitatory synapses in the hippocampus and other brain regions (Ayala et al, 2009; Rook et al, 2015; Sarihi et al, 2008; Sun et al, 2016) and can restore deficits in animal models in which synaptic plasticity and cognitive function are impaired (Bhardwaj et al, 2015; Lin et al, 2014; Waung and Huber, 2009; Won et al, 2012). …”
Section: Potential Antipsychotic and Cognition-enhancing Effects Of Mmentioning
confidence: 99%